Experience of using polymethyl methacrylate membranes for anti-HLA antibodies’ elimination by hemodialysis in renal transplant recipients - E. I. Pervakova; V. V. Vasilets; O. N. Rzhevskaya; N. V. Borovkova; A. V. Pinchuk (Трансплантология (Москва))
Introduction. In recipients with pre-existing sensitization with incompatible antigens of the main histocompatibility complex, the kidney graft survival after retransplantations directly depends on the level of anti-HLA antibodies. Despite many years of experience in using various methods: plasmapheresis, cascade filtration, immunosorption, intravenous administration of immunoglobulins, the use of polyclonal anti-lymphocytic agents, the search for more acceptable ways to reduce the level of anti-HLA antibodies still remains relevant nowadays.The purpose of the study was to assess the effect of polymethyl methacrylate membrane-based dialyzers on the decrease in anti-HLA antibody level in renal transplant recipients.Material and methods. The study included 20 kidney transplant recipients. The main study group consisted of 10 patients who underwent early postoperatoive hemodialysis using polymethyl methacrylate membrane-based dialyzers to decrease anti-HLA antibody level. A total of 53 hemodialysis procedures were performed, an average of 5.3 per patient. The comparison group included 10 recipients in whom plasmapheresis had been performed at similar timing after kidney transplantation aimed at reducing the anti-HLA antibody titers and whose data were studied retrospectively. A total of 38 plasmapheresis sessions were performed, an average of 3.8 per patient.Results. In the main study group, a day after the hemodialysis procedure using polymethyl methacrylate membranebased dialyzers the level of anti-HLA antibodies decreased by an average of 28.3% in 6 of 10 patients (60%), and increased in 4 cases. Meanwhile, in the comparison group, the level of anti-HLA antibodies in venous blood after a plasmapheresis session decreased average by 44.6% in 8 patients of 10 (80%), and increased in 2 cases, on the contrary. Of note, there were no significant differences between the patients of the two compared groups either in the number of positive results (p> 0.05, Fisher's exact test), or in terms of the decrease in anti-HLA antibody level (p> 0.05, Mann – Whitney test). On days 2 and 5, in 50% of cases both after the hemodialysis procedure using polymethyl methacrylate membranebased dialyzers and after the plasmapheresis session, the patients showed an increase in the anti-HLA antibodies level compared to the baseline values. In the remaining cases, the level of anti-HLA antibodies in both groups was recorded at a lower range compared to the baseline values.Conclusion. The use of polymethyl methacrylate membrane-based dialyzers in the renal allograft recipients having a high level of preexisting anti-HLA antibodies seems promising for the period of oligoanuria until the renal allograft function is restored, since both hemodialysis and the sorption of pre-existing (and also newly synthesized) antibodies take place simultaneously.